Omega-3 and omega-6 essential fatty acids: from their discovery to the therapeutic prospects - Carami, G. (Progress in Nutrition, 2007)
The essential fatty acids (EFA) are linoleic acid (omega-6 series) and a-linolenic acid (omega-3 series). The EFA levels of the mother represent a crucial point in the early stage of the new life, since an equilibrated ratio allows for an efficient conversion leading to g-linolenic acid (GLA), arachidonic acid (AA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). A plenty of literature data agree with the beneficial effects of omega-3 fatty acids, particularly in the case of an atherosclerotic coronary heart disease and other degenerative-chronic pathologies due to a chronic inflammatory condition.